PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS II SD NEGERI 010 SILIKUAN HULU KECAMATAN UKUI - Suharni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The problem in this research is the low student learning outcomes in Civics (PKn) in class II SD Negeri 010 Silikuan Hulu, which amounted to 65.33. Based on this, researchers conducted a study with the aim to improve student learning outcomes in PKn through the implementation of the STAD (Student Teams Achievement Divisions) type cooperative learning model. This research is a classroom action research conducted over two cycles, consisting of two meetings and a daily test in each cycle. The data collection technique used is the technique of observing activities of teachers and students and learning outcomes in PKn. The analysis technique used is descriptive analysis. The results showed that the application of the STAD cooperative learning model can increase the learning outcomes of students in PKn class II. This is supported by: (1) the activities of teachers has increased. In the first cycle, the first meeting obtained a score of 19 or 76.00% in the "good" category. At the second meeting of the first cycle, activities for teachers obtained a score of 21 or 84.00% in the "good" category. At the first meeting of the second cycle, activities for teachers obtained a score of 22 or 88.00% with a "very good" category. At the second meeting of the second cycle, activities for teachers obtained a score of 24 or 96.00% with a "very good" category. In addition, students also experienced an increase in activity. In the first meeting of the first cycle, the activity of the students obtained a score of 18 or 72.00% in the "good" category. Activities of students obtained a score of 21 or 84.00% in the "good" category. On the activities of students, a score of 23 or 92.00% was obtained with a "very good" category. In the second meeting, students obtained a score of 24 or 96.00% with a "very good" category; (2) The student learning outcomes in basic score students' average grades increased from 65.53 on the first cycle as much as 46.44% to 78.03 with the percentage thoroughly studied 82.14%, increased again in the second cycle as much as 60.70% to 81.96 with the percentage of 96.40% thoroughly studied. In addition, completeness of student learning outcomes also improved on the basis of the number of completeness score of students numbering 10 students or 35.70% with category yet complete and the first cycle increased with the number of 23 students or 82.14% with complete categories and the second cycle increases with the number of 27 students or 96.40% with a complete category.